Bias Kognitif dalam Keputusan Investasi di Pekanbaru - Restu Hayati; Azmansyah; Linda Hetri Suriyanti; Mimilientesa Irman (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2022)
This study aims to analyze the financial behavior of investors in terms of cognitive bias towards receiving information when making investment decisions in various financial securities. The method used is descriptive analysis with investors in Pekanbaru as a sample. The results of the study prove that in general, investors will behave normally. However, when faced with a variety of information, decision making will be quite biased when faced with a heuristic group. The level of investor bias will be very high in the reaction bias group. This group considers the existence of experience, different types of investment, as well as the delivery of information and a certain time will change investment needs after adjustments are made to the information.